(3GdeSFhdjI GdLfGFjI ddegfOS GdeYeGQi hebGhd GdHfGA (B/ s - (3eMeO YHOGdYXje YHOGdhgGH Ydi s; (3YeQ eMeO SGdes; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2010)
(3Ef ehVhY GdeSFhdjI GdLfGFjI ddegfOS GdeYeGQi hebGhd GdHfGA CUHM ai GdhbJ GdQGgf ef GdehVhYGJ PGJ GdGgejI GdHGdZI hPdc dGQJHGWI GQJHGWG hKjbG HMjGI GdCaQGO hhGbYge hETHGY MGLGJge GdHTQjI GdedMI Edi GdeSGcf hGdeQGab hcPdc dONhd LGfH GdESJKeGQ hJMbjb GdcSH GdeGOi ai gPG GdeLGd (B. (3hdPdc jLH Cf JTed gPg GdeSFhdjI cd TNU jbhe HOhQ ai YedjI GdHfGA adGHO Cf JTed GdegfOS HLejY JNUUGJg hGdebGhd ef GdHGWf hTQcGJ GdHfGA Hd hUGMH GdHfGA EPG cGf jbhe HOhQ ai YedjI GdHfGAs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2010s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B260-269s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdeSFhdjI GdLfGFjI s; (3GdegfOS GdeYeGQi s; (3ebGhd GdHfGA s; (3QcGFR GdeSFhdjI GdLfGFjIs; (3LQGFe GYeGd GdHfGA HWQjb GdYeOs; (3YedjI GdJTjjOs; (3GdYbhHGJ GdJbdjOjI aj eLGd LQGFe GdHfGAs; (3OhQ GdegfOS ai YedjjI GdJTjjOs; (3GdeSFhdjI Yf GdNWC ai GdJfajPs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs